NSF- and SNARE-mediated membrane fusion is required for nuclear envelope formation and completion of nuclear pore complex assembly in Xenopus laevis egg extracts. - Baur, T; Ramadan, K; Schlundt, A; Kartenbeck, J; Meyer, H (2007)
Despite the progress in understanding nuclear envelope (NE) reformation after mitosis, it has remained unclear what drives the required membrane fusion and how exactly this is coordinated with nuclear pore complex (NPC) assembly. Here, we show that, like other intracellular fusion reactions, NE fusion in Xenopus laevis egg extracts is mediated by SNARE proteins that require activation by NSF. Antibodies against Xenopus NSF, depletion of NSF or the dominant-negative NSF(E329Q) variant specifically inhibited NE formation. Staging experiments further revealed that NSF was required until sealing of the envelope was completed. Moreover, excess exogenous alpha-SNAP that blocks SNARE function prevented membrane fusion and caused accumulation of non-flattened vesicles on the chromatin surface. Under these conditions, the nucleoporins Nup107 and gp210 were fully recruited, whereas assembly of FxFG-repeat-containing nucleoporins was blocked. Together, we define NSF- and SNARE-mediated membrane fusion events as essential steps during NE formation downstream of Nup107 recruitment, and upstream of membrane flattening and completion of NPC assembly.